The Influence of Government Regulation No. 46 Year 2013 to Tax Income Revenue (Case in Kantor Wilayah DJP Jatim III) - Lathiefa Rusli; Candra Fajri Ananda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Tax is a main source that has big contribution to national income. Around 70% national income is dominated by tax revenue. DJP, under Ministry of Financial, is a financial institution that controls the tax reformation to stabilize economy as the function of fiscal policy in Indonesia. The research objective is to analyze the influence of Government Regulation No. 46 year 2013 to tax revenue, tax effort, and tax buoyancy in Kanwil DJP Jatim III. Descriptive quantitative method by using panel data regression was used to analyze the influence of independent variables to dependent variable. Result of the research showed that Government Regulation No. 46 year 2013 was not an effective tax policy. Variables NPIT and OPIT did not influence the tax revenue, while variable CIT significantly positive influenced to tax revenue. Besides, after the implementation of Government Regulation No. 46 year 2013, the tax effort and tax buoyancy were influenced by the change on GDP and the change on tax capacity. Keywords: Government Regulation No. 46, taxpayers, tax effort, tax buoyancy